Establishing a Small Planting of Native Wildflowers from Seed - Jeffrey G. Norcini (EDIS, 2007)
ENH-1046, a 3-page illustrated fact sheet by Jeffrey G. Norcini, describes 12 steps for establishing a small landscape planting of native wildflowers. Plantings can range in size from a small spot in a yard to a "mini-meadow." Includes references. Published by the UF Department of Environmental Horticulture, December 2006.